Performing Representativity, Expanding Democracy: Human Rights as a Blueprint to Demand Voting Rights for Non-citizen Migrants - Toscano, Javier (Public Governance, Administration and Finances Law Review, 2024)
The right to vote stands as a cornerstone in contemporary liberal democracies, but its limits, particularly regarding who holds this privilege, remains a contentious issue, pitting democracy against the intricate dynamics of migration. Acknowledging this tension, this article asserts that a more illuminating perspective on the nexus between voting rights, migration and democracy emerges when viewed through the lens of human rights, as opposed to the conventional framework of citizenship rights. The article develops a theoretical framework based on a practical case from Germany, where the Demokratie für Alle movement advocates for voting rights for non-citizens, underlining thus the importance of a human-rights-based framework in shaping political demands. The article explores the articulation of a practice and the emergent theory upon which it can be sustained, exploring thus the concept of a performing representativity within an actual and evolving context.